2018
DOI: 10.1371/journal.pone.0196305
|View full text |Cite
|
Sign up to set email alerts
|

Dental color measurement to predict DNA concentration in incinerated teeth for human identification

Abstract: Teeth exposed to thermal stress can shed light on the identification of incinerated individuals and on the circumstances of the fire. Changes in the color of burned teeth can provide information on structural changes and the temperature of exposure. The objective of this study was to correlate color modifications with the concentration of human DNA in teeth burned at different temperatures. Spectrophotometry was used to measure the color of 40 teeth heated at temperatures of 100, 200, and 400°C for 60 min. DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…7 Based on this background, the uses of Laser from Raman Spectrocopy in dentistry can be in the form of sex examination of tooth samples 4 , examination of the biological elements of ancient teeth 8 , estimation of age from tooth samples 9 , Spectrophotometric analysis of burnt tooth color can predict the feasibility of human DNA extraction for identification purposes. 10 However, there is a lack of evaluation of the laser effect of Raman spectra on the purity of amelogenin DNA from dental samples. The purpose of this study was to determine the impact of laser application from Raman spectroscopy on the concentration and purity of DNA amelogenin for gender identification.…”
Section: Introductionmentioning
confidence: 99%
“…7 Based on this background, the uses of Laser from Raman Spectrocopy in dentistry can be in the form of sex examination of tooth samples 4 , examination of the biological elements of ancient teeth 8 , estimation of age from tooth samples 9 , Spectrophotometric analysis of burnt tooth color can predict the feasibility of human DNA extraction for identification purposes. 10 However, there is a lack of evaluation of the laser effect of Raman spectra on the purity of amelogenin DNA from dental samples. The purpose of this study was to determine the impact of laser application from Raman spectroscopy on the concentration and purity of DNA amelogenin for gender identification.…”
Section: Introductionmentioning
confidence: 99%
“…The survival of dental DNA is highly dependent on the temperature and duration of the heat exposure 13 15 . It has generally been reported that dental DNA can withstand temperatures up to 400 °C for one hour but that its quantity and quality are superior after exposure to lower temperatures for shorter time periods (1–20 min), facilitating forensic identification 9 .…”
Section: Introductionmentioning
confidence: 99%